Telescopic double crowns in prosthodontics - Kara, Recep (International Journal of Dental Research, 2021)
The purpose of this article is to classify the types of telescopic prostheses that protect natural teeth as an alternative to traditional removable prostheses, and to explain their advantages, disadvantages, indications and clinical significance in order to minimize the problems of removable dentures. Telescopic prostheses consist of an inner (primary) crown permanently cemented to an abutment and an outer (secondary) crown attached to the prosthesis. Primary crowns protect the abutment from bruises and thermal irritation, and also provide retention and stabilization of the secondary crown. The secondary crown combines the primary crown with the prosthesis to form a telescopic unit, providing prosthetic retention and stability.Â Â